Diseño y Aplicación de un Programa de Capacitación para docentes sobre la Psicopedagogía que se debe emplear en la Discapacidad Intelectual en adolescentes de la Unidad Educativa San Patricio durante el periodo marzo- julio 2017. - Calderón Saltos, Nuvia Alejandra (2018)
The Design and Application of a Training Program for Psychopedagogy Teachers that must be applied in Adolescents with Intellectual Disability at San Patricio School, from March to July 2017, emerged as an answer to the lack of Adolescent Intellectual Disability training programs at this school. Due to this, the Teachers didn´t have the needed psychopedagogical resources to treat their students’ needs. The approach given to the project is inclusive and is in agreement with what is said in the Convention on the Rights of Persons with Disabilities. The purpose of the project is to create a reflection of the Intellectual Disabilities. The purpose of the project is to create a reflection of the Intellectual Disability in the teacher of San Patricio School, that provokes an attitudinal change among them. The project was developed in two stages. The first one was the theoretical stage in which all the topics that involve the Intellectual Disability were mentioned. The second one was the practical stage in which the teachers must implement the theoretical concepts in practice through daily-life and problem- solving activities, and thoughtful videos. The theoretical stage gives teachers new tools and techniques to work with students with Intellectual Disability. In the same way, in the practical stage the teachers must create new tools based on the new theoretical knowledge.